2017
DOI: 10.1007/s00484-016-1284-y
|View full text |Cite
|
Sign up to set email alerts
|

Different responses of influenza epidemic to weather factors among Shanghai, Hong Kong, and British Columbia

Abstract: Weather factors have long been considered as key sources for regional heterogeneity of influenza seasonal patterns. As influenza peaks coincide with both high and low temperature in subtropical cities, weather factors may nonlinearly or interactively affect influenza activity. This study aims to assess the nonlinear and interactive effects of weather factors with influenza activity and compare the responses of influenza epidemic to weather factors in two subtropical regions of southern China (Shanghai and Hong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
25
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 36 publications
5
25
1
1
Order By: Relevance
“…A signi cant wet effect on in uenza activity was observed in Chongqing, which is consistent with previous studies 12, [20][21][22][23] . Experimental study has shown stronger infectivity of in uenza virus in a high relative humidity 24 .…”
Section: Discussionsupporting
confidence: 92%
“…A signi cant wet effect on in uenza activity was observed in Chongqing, which is consistent with previous studies 12, [20][21][22][23] . Experimental study has shown stronger infectivity of in uenza virus in a high relative humidity 24 .…”
Section: Discussionsupporting
confidence: 92%
“…A decline of 1°C in temperature increased influenza infections risk by 11% in Finland (Jaakkola et al, 2014). Moreover, 1°C decrease of temperature cased a rising of 8.55% in influenza cases in Hong Kong, and an increase of 32.14% in the UK (Wang et al, 2017). Low temperature may lengthen the survival of influenza virus, and lead to increasing contact rates through more people indoor crowding (Cheng et al, 2016;Liao et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…There are different responses of influenza to climate factors in different climate zones. The area with temperate climate appeared to have greater risk in temperature and humidity, compared to subtropical regions (Wang et al, 2017). The author reported that this may due to a lower mean temperature and humidity in temperate areas than that in subtropical regions.…”
Section: N=100%mentioning
confidence: 93%
See 1 more Smart Citation
“…Non-linear models have been widely used in assessing the relationships between meteorological factors and health outcomes (Peng et al, 2017;Wang et al, 2017). Meanwhile, most studies found the lagged effects of meteorological factors (Antunes et al, 2017;Seposo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%